Thermal Stability and Molecular Ordering of Organic Semiconductor Monolayers: Effect of an Anchor Group. Issue 8 (31st March 2015) - Jones, Andrew O. F.; Knauer, Philipp; Resel, Roland; Ringk, Andreas; Strohriegl, Peter; Werzer, Oliver; Sferrazza, Michele
Abstract: The thermal stability and molecular order in monolayers of two organic semiconductors, PBI‐PA and PBI‐alkyl, based on perylene derivatives with an identical molecular structure except for an anchor group for attachment to the substrate in PBI‐PA, are reported. In situ X‐ray reflectivity measurements are used to follow the stability of these monolayers in terms of order and thickness as temperature is increased. Films have thicknesses corresponding approximately to the length of one molecule; molecules stand upright on the substrate with a defined structure. PBI‐PA monolayers have a high degree of order at room temperature and a stable film exists up to 250 °C, but decomposes rapidly above 300 °C. In contrast, stable physisorbed PBI‐alkyl monolayers only exist up to 100 °C. Above the bulk melting point at 200 °C no more order exists. The results encourage using anchor groups in monolayers for various applications as it allows enhanced stability at the interface with the substrate. Abstract : Tie your monolayer down: In situ X‐ray reflectivity measurements are used to follow the structural evolution of monolayer organic semiconductor films with increasing temperature. Using an anchor group in the monolayers is found to add significantly to their stability at elevated temperatures when compared to monolayers with an identical structure without an anchor group.